What Is the US Comparative Advantage in Entrepreneurship? Evidence from Israeli Migration to the United States - Conti, Annamaria; Guzman, Jorge A. (The Review of Economics and Statistics, 2023)
Abstract We investigate underlying sources of the US entrepreneurial ecosystem's advantage compared to other innovative economies by assessing the benefits that Israeli startups derive from migrating to the United States. Addressing positive sorting into migration, we show that migrants raise larger funding amounts and are more likely to have a U.S. trademark and be acquired than nonmigrants. Migrants also achieve a higher acquisition value. However, their patent output is not larger. We conclude that the United States entrepreneurial ecosystem's advantage vis-à-vis other innovative economies arises from several sources producing sizeable gains for startups. These sources are investor availability as well as large consumer and acquisitions markets.